Cancer and the Immune System: Basic Concepts and Targets for Intervention - Pardoll, Drew (Seminars in oncology, 2015)
A number of consensuses regarding cancer immunology have recently emerged from both preclinical immunotherapy models and analysis of cancer patients. First and foremost, the natural state of endogenous tumor reactive T cells is characterized by general hyporesponsiveness or anergy. This is likely due to a number of mechanisms that tumors use to induce tolerance as they develop. While many of the newer generation vaccines can effectively transfer antigen to and activate dendritic cells, T-cell tolerance remains a major barrier that is difficult to overcome by vaccination alone. Preclinical models demonstrate that for poorly immunogenic tumors, once tolerance has been established, therapeutic vaccines alone are ineffective at curing animals with a significant established tumor burden. However, combination strategies of vaccination together with inhibitors of immunologic checkpoints and agonists for co-stimulatory pathways are proving capable of overcoming tolerance and generating significant anti-tumor responses even in cases of established metastatic cancer.